Similarity Forces and Recurrent Components in Human Face-to-Face Interaction Networks - Flores, Marco Antonio Rodríguez; Papadopoulos, Fragkiskos (My University, 2018)
We show that the social dynamics responsible for the formation of connected components that appear recurrently in face-to-face interaction networks find a natural explanation in the assumption that the agents of the temporal network reside in a hidden similarity space. Distances between the agents in this space act as similarity forces directing their motion towards other agents in the physical space and determining the duration of their interactions. By contrast, if such forces are ignored in the motion of the agents recurrent components do not form, although other main properties of such networks can still be reproduced.
Keywords: Social dynamics; Interaction networks; Psychological model